Goats’ Performance in Unsolvable Tasks Is Predicted by Their Reactivity Toward Humans, but Not Social Rank - Yoshida, Naoya; Koda, Naoko (Frontiers in Psychology, 2020)
In order to clarify the ability of animals to communicate with humans, it is necessary to examine the behaviors of animals directed at humans, taking into account individual differences. This study investigated whether the behaviors of goats (Capra hircus) can be predicted when given an unsolvable task. Two experiments were performed in a paddock using 16 domesticated goats. In Experiment 1, behavioral tests were conducted to determine the goats’ social rank and reactivity toward a stranger. In Experiment 2, the goats’ behaviors in an unsolvable task and two control conditions in which either only a human or bucket was presented were examined. The behaviors of the goats were video-recorded and compared between the conditions. Then, we examined whether the behaviors of goats in the presence of both the human and unsolvable task can be predicted from the scores for social rank and reactivity toward humans. Compared with the control conditions, the goats increased physical contact with the human, but did not increase gazing. It is possible that differences in individual characteristics and long-term experiences with humans can lead to differences in human-directed behaviors of animals. Although the social rank order of the goats was clearly linear, there was no correlation between their behaviors in the unsolvable task and their social rank. The goats that tended to interact with the stranger in Experiment 1 were more likely to approach and establish contact with the human in the unsolvable task than goats that reacted more averse toward humans. There was no association between the level of reactivity toward the stranger and the goats’ involvements in the unsolvable task. Therefore, it is possible that the goats which increased interactions with humans did not necessarily have low motivation to engage in unsolvable tasks, but relied on humans as a means of communication. In conclusion, the behavioral changes and its diversity as the responses toward short-term changes in the environment, such as the presence or absence of humans and unsolvable tasks, were related to differences in individual behavioral characteristics (i.e. reactivity toward humans).